2004
DOI: 10.1093/ilar.45.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in the Female: Role of Biological Sex and Estrogen

Abstract: Women are protected from stroke relative to men until the years of menopause. Because stroke is the leading cause of serious, long-term disability in the United States, modeling sex-specific mechanisms and outcomes in animals is vital to research. Important research questions are focused on the effects of hormone replacement therapy, age, reproductive status, and identification of sex-specific risk factors. Available research relevant to stroke in the female has almost exclusively utilized rodent models. Gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 125 publications
6
84
0
Order By: Relevance
“…This is in contrast to the benefits of female gender and of estrogen in ischemic injury in unconditioned rodent brain (for a review, see Murphy et al, 2004). The overall neuroprotective results described in these experimental animal studies with estrogen in unconditioned ischemic brain have been reflected in some of the earlier clinical trials (for a review, see Langer, 2002), but the results of more recent clinical studies have raised the issue that there are unanticipated and paradoxical effects of estrogen as it is currently administered in women (for a review, see Murphy et al, 2004). Several more recent experimental studies would also suggest that estrogen might not be universally neuroprotective in cerebral ischemia in unconditioned brain (Bingham et al, 2005;Carswell et al, 2004;Gordon et al, 2005;Santizo et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…This is in contrast to the benefits of female gender and of estrogen in ischemic injury in unconditioned rodent brain (for a review, see Murphy et al, 2004). The overall neuroprotective results described in these experimental animal studies with estrogen in unconditioned ischemic brain have been reflected in some of the earlier clinical trials (for a review, see Langer, 2002), but the results of more recent clinical studies have raised the issue that there are unanticipated and paradoxical effects of estrogen as it is currently administered in women (for a review, see Murphy et al, 2004). Several more recent experimental studies would also suggest that estrogen might not be universally neuroprotective in cerebral ischemia in unconditioned brain (Bingham et al, 2005;Carswell et al, 2004;Gordon et al, 2005;Santizo et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Studies on sex differences in stroke in humans are few, focusing primarily on incidence, age of first stroke and outcome. A number of studies have documented that women are "protected" against stroke relative to men -at least until the years of menopause, when estrogen levels decline due to follicular depletion and stroke incidence increases in women [10][11][12][13]. Intriguingly, stroke outcome in postmenopausal women has been shown in several studies to be worse as compared to males, with postmenopausal women having a significantly higher disability and fatality rate as compared to men [11][12][13][14].…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…A recent review of randomized and non-randomized trials evaluating gender and age and stroke risk following CEA concluded that operative stroke risk is increased in women independent of age [40]. While gender and age are known to alter experimental ischemic brain outcomes [41,42], few studies have examined gender and age in preconditioned brain exposed to ischemic and other types of brain injury.…”
Section: Gender and Age Effects On Preconditioningmentioning
confidence: 99%